2018
DOI: 10.1055/s-0038-1670700
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Frequency Lowering Technology in the Treatment of Severe-to-Profound Hearing Loss: A Review of the Literature and Candidacy Considerations for Clinical Application

Abstract: This article provides a review of the current literature on the topic of frequency lowering hearing aid technology specific to the treatment of severe and profound levels of hearing impairment in child and adult listeners. Factors to consider when assessing listener candidacy for frequency lowering technology are discussed. These include factors related to audiometric assessment, the listener, the type of hearing aid technology, and the verification and validation procedures that can assist in determining cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In this study, the average CT1s were 3.77 kHz (SR2 default) and 2.17 kHz (SR2 strong), suggesting that a lower cut-off frequency for SR2 could limit recognition performance. The better performance with SR2 default than SR2 strong suggested that there might be an optimal range of frequency compression for individuals with high-frequency hearing loss, as suggested by several previous studies (Johnson and Light, 2015;Scollie et al, 2016;Glista and Scollie, 2018).…”
Section: Discussionmentioning
confidence: 61%
“…In this study, the average CT1s were 3.77 kHz (SR2 default) and 2.17 kHz (SR2 strong), suggesting that a lower cut-off frequency for SR2 could limit recognition performance. The better performance with SR2 default than SR2 strong suggested that there might be an optimal range of frequency compression for individuals with high-frequency hearing loss, as suggested by several previous studies (Johnson and Light, 2015;Scollie et al, 2016;Glista and Scollie, 2018).…”
Section: Discussionmentioning
confidence: 61%